Synthesis, working mechanism, and effectiveness of a novel corrosion‐inhibiting polycarboxylate superplasticizer for concrete. (October 2016) - Xu, Qingtao; Gao, Heping; Zeng, Jun; Chen, Cheng; Zhou, Wei; Wang, Suqin; Tian, Xingxing; Peng, Yinxian
ABSTRACT: In this work, a novel corrosion‐inhibiting polycarboxylate superplasticizer for concrete was synthesized through two‐step esterification reaction and one‐step polymerization. Firstly, arginine‐polyethylene glycol monoester was synthesized by p ‐toluenesulphonic acid‐catalyzed esterification reaction of one hydroxyl of polyethylene glycol and carboxylic of arginine containing the main functional group of corrosion‐inhibiting polycarboxylate superplasticizer. Secondly, under the condition of hydroquinone as a polymerization inhibitor, polycarboxylate macromonomer was also synthesized by p ‐toluenesulphonic acid‐catalyzed esterification reaction of another hydroxyl of as‐prepared monoester and carboxylic of methyl acrylic acid (96 % esterification rate). Finally, a corrosion‐inhibiting polycarboxylate superplasticizer for concrete was synthesized by ammonium peroxydisulphat‐initiated polymerization, polycarboxylate macromonomer, methyl acrylic acid, and sodium methyl acrylic acid. The structures of monoester, macromonomer, and superplasticizer were characterized by FTIR. Moreover, the fluidity of cement paste, the water reduction, and the compressive strength ratio of as‐prepared polycarboxylate macromonomer (0.5 %) as a corrosion‐inhibiting superplasticizer were more than 290 mm, 25 %, and 130 % respectively.